Partial factors and reliability verification for the site load factor approach for the assessment of existing bridges. (October 2021) - Pérez Sifre, Sergi; Lenner, Roman
Abstract: Fundamental concepts of the developed site load-factor approach for the assessment of existing bridges are introduced in this contribution. The method is complemented by the calibration of the partial factors accounting for uncertainties. The calibration is crucial for the simple application of the method in concordance with semi-probabilistic approaches commonly presented in design guidelines. As means of verification of the proposed methodology, a reliability analysis of the site load factor approach is offered to assure that the intended safety level required by codes is achieved. Results indicate that reductions of the static load effects mandated by design stipulations can be implemented, while maintaining the required safety levels. The methodology presented here is developed in the context of data collected in South Africa, nevertheless the framework is general and can be extrapolated to any other country or dataset.